Factors Influencing EFL Students' Engagement in Project-Based Learning within ICT-Integrated Classrooms - Ardhita Annisa Dewi; Roslaini Roslaini (JELITA, 2024)
Willingness is a kind of awareness of students to participate in a study. It is important to have for students, particularly in learning ICT-based projects. Then, this research aims to investigate the factors of students’ willingness that influence them to complete the project. This research used a mixed–method design, and the data were collected using open and close-ended questions. Thirty EFL students participated in this study as respondents. After analyzing the data using the Likert scale, the result shows that EFL students' willingness to engage in projects is significantly positive. After calculating the frequency and the percentage of students’ responses, the highest percentage for behavioral factors is (66,7%), task orientation (96,7%), teacher support (60%), enjoyment task (50%), achievement (60%), and emotional engagement (53,3%). In this case, it indicates a significant tendency among students to tackle challenges.